2011
DOI: 10.1177/0265407511431055
|View full text |Cite
|
Sign up to set email alerts
|

A brief history of social scientists’ attempts to measure passionate love

Abstract: The concept of passionate love has a long history, yet it was not until the 1940s that social scientists created tools designed to measure this emotion. Over the next 60 years, numerous scales of romantic and passionate love were created and tested. Currently, however, there exists no single compendium of existing scales. This paper attempts to fill in the missing information on existing love scales by providing a list of 33 different measures and indicating where each scale's reliability and validity informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
13

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 70 publications
0
52
0
13
Order By: Relevance
“…The JLS was designed to assess cognitive, emotional and behavioral signs of passionate love 8,10 . Cognitive components consist of [1] intrusive thought or concern for the partner; [2] idealization of the other or the relationship; and [3] desire to get to know each other and be known by him/her.…”
Section: Juvenile Love Scale (Jls)mentioning
confidence: 99%
See 1 more Smart Citation
“…The JLS was designed to assess cognitive, emotional and behavioral signs of passionate love 8,10 . Cognitive components consist of [1] intrusive thought or concern for the partner; [2] idealization of the other or the relationship; and [3] desire to get to know each other and be known by him/her.…”
Section: Juvenile Love Scale (Jls)mentioning
confidence: 99%
“…Hatfield et al 8 found 33 instruments measuring romantic love over the last 70 years approximately. These measures were elaborated by different areas of expertise such as Sociology, Psychology, Anthropology, Medicine, Biology and Neurosciences.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, Marks (1994, p. 854) scholars with an interest in social relationships may draw benefits from a sociological approach that locates the understanding and experience of human relationships historically and socially. For example, Hatfield, Bensman, & Rapson (2012) demonstrate how the concept of passionate love has occupied psychologists and other social scientists for decades, typically with a view to measuring it. In reviewing this field of activity, Hatfield et al (2012) demonstrate how scholars' conceptions of the nature of love have changed over the years, and how historical and scientific changes about love are interconnected, reflected in the various scales designed to measure passionate love.…”
Section: Workplace Friendships As Social Relationshipsmentioning
confidence: 99%
“…For example, Hatfield, Bensman, & Rapson (2012) demonstrate how the concept of passionate love has occupied psychologists and other social scientists for decades, typically with a view to measuring it. In reviewing this field of activity, Hatfield et al (2012) demonstrate how scholars' conceptions of the nature of love have changed over the years, and how historical and scientific changes about love are interconnected, reflected in the various scales designed to measure passionate love. Such research findings are in tune with a sociology of friendship that alerts us to how ongoing historical and social change impacts on relationships, but also how such changes shape bodies of knowledge on relationships generated within different academic disciplines using specific research techniques and theories.…”
Section: Workplace Friendships As Social Relationshipsmentioning
confidence: 99%
“…(Case, 1839, cited in Taylor & Lasch, 1963 Elsewhere, the idea of a kindred spirit is appealed to as a way to illustrate the closeness and similarity of the artistic relationship between the poet William Cullen Bryant and the poet Thomas Cole (Ringe, 1954). These notions of similarity, sharedness, friendship are also found in philosophical and theoretical understandings of love -a topic of research which has dramatically broadened and deepened more recently to emphasize its multi-faceted appearance (Hatfield et al, 2012). It is to these we now turn in the hope of further shedding light on this hard-to-grasp phenomenon of kindred spirit connection.…”
Section: Examining the Literaturementioning
confidence: 99%